La economía cocalera en el Perú: implicancias sobre las migraciones y el medio ambiente - Montero, Jorge Luis (1995)
The author addresses the problem of determining the scale of the coca economy in Peru and its effects on the environment and inter-regional migration. To do so, he bases his findings on information from the last population and agricultural censuses. He also suggests a series of arguments that help the reader focus on this problem of national dimensions.